Hollow polydopamine nanoparticles loading with peptide RL-QN15: a new pro-regenerative therapeutic agent for skin wounds - Sun, Huiling; Wang, Ying; He, Tiantian; He, Dingwei; Hu, Yan; Fu, Zhe; Wang, Yinglei; Sun, Dandan; Wang, Junsong; Liu, Yixiang; Shu, Longjun; He, Li; et al. (Journal of nanobiotechnology, 2021)
Although the treatments of skin wounds have greatly improved with the increase in therapeutic methods and agents, available interventions still cannot meet the current clinical needs. Therefore, the development of new pro-regenerative therapies remains urgent. Owing to their unique characteristics, both nanomaterials and peptides have provided novel clues for the development of pro-regenerative agents, however, more efforts were still be awaited and anticipated. In the current research, Hollow polydopamine (HPDA) nanoparticles were synthesized and HPDA nanoparticles loading with RL-QN15 (HPDAlR) that was an amphibian-derived peptide with obvious prohealing activities were prepared successfully. The characterization, biodistribution and clearance of both HPDA nanoparticles and HPDAlR were evaluated, the loading efficiency of HPDA against RL-QN15 and the slow-releasing rate of RL-QN15 from HPDAlR were also determined. Our results showed that both HPDA nanoparticles and HPDAlR exerted no obvious toxicity against keratinocyte, macrophage and mice, and HPDA nanoparticles showed no prohealing potency in vivo and in vitro. Interestingly, HPDAlR significantly enhanced the ability of RL-QN15 to accelerate the healing of scratch of keratinocytes and selectively modulate the release of healing-involved cytokines from macrophages. More importantly, in comparison with RL-QN15, by evaluating on animal models of full-thickness injured skin wounds in mice and oral ulcers in rats, HPDAlR showed significant increasing in the pro-regenerative potency of 50 and 10 times, respectively. Moreover, HPDAlR also enhanced the prohealing efficiency of peptide RL-QN15 against skin scald in mice and full-thickness injured wounds in swine. HPDA obviously enhanced the pro-regenerative potency of RL-QN15 in vitro and in vivo, hence HPDAlR exhibited great potential in the development of therapeutics for skin wound healing.